The bitter truth - Williams, Shanora (Dafina, 2024)
"An upstanding political candidate. A determined stalker. A shattering lost weekend. Now, when his worst secret comes calling, how far will one man's elegant, all-too-devoted wife go to uncover the truth... or bury it? For Jolene 'Jo' Baker, the least she can do for her adoring husband, Dominic, is give unwavering support for his North Carolina gubernatorial run. He is not only the love of her life, he's also helping her prove that she's far more than just a pampered trophy wife. With huge crowds showing up at Dominic's speeches and the polls consistently in his favor, she's never been happier to stand proudly by his side... Until she and Dominic start seeing the same, strangely ominous woman turning up all along the campaign trail. Until their tour starts becoming a nightmare of botched events, crucial missed information, and increasingly dangerous 'accidents.' Suddenly Jo can't get any answers from Dominic- or understand why he is acting so paranoid and terrified... What Jo can do is start digging into his past--one she's never really questioned beyond his perfect image and dazzling accomplishments. What results is an alarming series of events that leave her baffled: Good friends turn into enemies, truths are revealed to be lies, and all clues lead back to one secret, shattering weekend that changes Jo's entire life. With her world splintering into pieces, can Jo risk trying to set things right? Or will hiding the bitter truth by any means necessary destroy her as well?" -- Page 4 of cover.